Alternatives to Christian education. Atheist propaganda in Romanian schools during the communist period (The case of Mureș County) - Pășcan, Sabin-Gavril (Technium Social Sciences Journal, 2023)
The communist regime in our country imposed atheism on the masses. In a state where morality and common sense were deeply linked to religion (Christian-Orthodox, Mosaic or Islamic) the concerted attacks by the communist regime, following the Stalinist model in the USSR of the 1920s, emptied people's conscience of any natural value scale. After the Second World War and the establishment of the communist regime in Romania, the influence of churches and religious institutions in public education was significantly reduced, and denominational schools were abolished or transformed into state schools. The education reform of 1948 also had an important impact on confessional education in Mureș County.